IMPLEMENTASI UPAYA DIVERSI PADA TINGKAT PENYIDIKAN TERHADAP TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA YANG DILAKUKAN ANAK (STUDI DI POLRESTABES MEDAN) - Indira Muliani (Jurnal Mahupiki, 2019)
Indira Muliani* Edi Yunara** Rafiqoh Lubis*** Criminal act of narcotics abuse carried out by children, have to get special attention in its resolution. One of the efforts to overcome the crime of narcotics abuse by children is through the implementation of the juvenile justice system. The purpose of implementing the criminal justice system is not merely to impose criminal sanctions on children of criminal offenders, but rather focus on the rationale that the imposition of sanctions is a means to support the welfare of child offenders. The juvenile justice system recognizes the term restorative justice. Restorative justice is the aim of implementing diversion in the juvenile justice system. Diversion is the transfer of settlement of Child cases from criminal justice processes to processes outside of juvenile justice. Diversion can be done at the level of investigation, the level of prosecution and at the stage of the court examination. Diversion at the investigation level was conducted to find and collect evidence. The research method used is a normative juridical research method, and the data used are primary data and secondary data. Then the primary data and secondary data are analyzed qualitatively. Diversion for child offenders is to provide a better alternative than the official procedure of proceedings in court. Diversion in national legal instruments began since the inception of legislation No. 11 of 2012 about the Child Criminal Justice System is also regulated in Government Regulation No. 65 of 2015 regarding Guidelines for Diversifying and Handling of Children who are not yet twelve years old, and the existence of an internal regulation in the form of Court Regulation No. 4 of 2014 regarding Guidelines for Implementing Diversion in the Child Criminal Justice System and Attorney General's Regulation No. 6 of 2015 regarding Guidelines for Implementing Diversion at the Prosecution Level and Secret Telegram Letters from the PolriKabareskrim. The implementation of diversion efforts at the investigation level at the Medan Polrestabes is based on legislation No. 11 of 2012 regarding the Child Criminal Justice System. Diversion is carried out by investigators who begin with the presence of the police, the implementation of diversion deliberations and ends with the approval of determination of diversion to the court. Determination of diversion issued by the Medan District Court on this diversion attempt is Number: 6 / PENT.PID.Sus-Anak / 2018 / PN.MDN. The obstacle in implementing diversion in Medan Polrestabes comes from community factors, that is the lack of caring from parents.Keywords : Diversion, Investigation, Narcotics Abuse *Student at Faculty of Law USU **Supervisor I, Lecturer at Faculty of Law USU ***Supervisor II, Lecturer at Faculty of Law USU